2014
DOI: 10.1111/gcbb.12137
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis biochar systems, balance between bioenergy and carbon sequestration

Abstract: This study aimed to investigate the extent to which it is possible to marry the two seemingly opposing concepts of heat and/or power production from biomass with carbon sequestration in the form of biochar. To do this, we investigated the effects of feedstock, highest heating temperature (HTT), residence time at HTT and carrier gas flow rate on the distribution of pyrolysis co-products and their energy content, as well as the carbon sequestration potential of biochar. Biochar was produced from wood pellets (WP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 40 publications
5
51
0
Order By: Relevance
“…It is reported that the magnitude of secondary (char) reactions is mainly influenced by the intensity and duration of contact of vapours with feedstock / biochar [37,39] as longer vapour residence times increase biochar yields [40]. This means that reduced hot vapour residence time, besides reducing biochar formation [23], should also reduce PAH formation as already speculated in McGrath et al…”
Section: Effect Of Carrier Gas Flow and Residence Time On Pahs In Biomentioning
confidence: 75%
See 1 more Smart Citation
“…It is reported that the magnitude of secondary (char) reactions is mainly influenced by the intensity and duration of contact of vapours with feedstock / biochar [37,39] as longer vapour residence times increase biochar yields [40]. This means that reduced hot vapour residence time, besides reducing biochar formation [23], should also reduce PAH formation as already speculated in McGrath et al…”
Section: Effect Of Carrier Gas Flow and Residence Time On Pahs In Biomentioning
confidence: 75%
“…In a batch-reactor with no carrier gas flow, the gas-solid residence time for secondary reactions to take place is maximized [23,40]. Higher carrier gas flow decreases the hot vapour residence time which results in decreased PAH formation [35].…”
Section: Effect Of Carrier Gas Flow and Residence Time On Pahs In Biomentioning
confidence: 99%
“…Typically, an approximate 40 to 60% of biomass C would be carbonized to biochar during pyrolysis, and the remaining C would be retained in liquid and gaseous coproducts (Crombie et al, 2014; Ling et al, 2013). The initial conversion process requires high energy to ignite the pyrolysis temperature to 400 to 650°C (Crombie and Mašek, 2013; Vardon et al, 2013). Therefore, it is challenging to produce biochar more efficiently for C sequestration than burying biomass in soils.…”
mentioning
confidence: 99%
“…While pyrolysis is a process that excludes the additional input of an oxidant stream and thus exposes the produced biochar to its own product gas, gasification uses a sub-stoichiometric amount of oxidant (commonly air or steam), which has an enormous impact on the biochar characteristics. Hydrothermal carbonization occurs in a liquid environment under pressure, which also results in very different chars compared to the chars created in a gaseous environment, see, e.g., [35,36].…”
Section: Production-dependent Biochar Propertiesmentioning
confidence: 99%